Jean-Antoine-Nicolas Caritat, marquis de Condorcet, papers - Condorcet, Jean-Antoine-Nicolas de Caritat, marquis de, 1743-1794.
First and second holograph drafts of Condorcet's Eloge of Benjamin Franklin, with a secretary's final copy, annotated by Condorcet.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
In part, handwritten transcripts.
French philosopher, mathematician, and politician.
Collection material in French.
Keywords: Franklin, Benjamin, -- 1706-1790.; France -- Foreign relations -- United States; Mathematicians; Philosophers; Politicians